Correspondence - Bourne, St. Clair; Abrahams, Peter; Sachs, Charles W.; Bayless, Warren; Engel, Fred; Heezell, M. P.; Chambers, William; Bricker, Herschel (My University, 1986)
Correspondence involving film and theater
34 pgs. Typescript, handwritten, pictures, sepia-toned, in fragile condition.
Keywords: Business - Correspondence; Letters